Spiritual and moral reform of Muslim inmates: the model of Bediuzzaman Said Nursi (1878-1960) - Bensaid, Benaouda (2010)

(untitled)
This paper discusses some of the fundamental concepts and strategies pertaining to the reform of Muslim inmates in light of Nursi’s perspective of change. Nursi lays the foundation for the comprehensive spiritual and moral reform of Muslim inmates, based on a set of concepts and themes such as the purpose of life, human nature, the notion of the ‘expansion of time’, and good and evil. Nursi’s plan of reform for Muslim inmates makes use of the Risale-I Nur to provide both a cognitive and moral shaping of inmates, in addition to an enhancement of their personality in the context of spiritual remembrance and brotherhood between inmates. A comprehension of Nursi’s program of inmates’ reform first enhances our understanding regarding the best approaches towards the effective therapy, reform and rehabilitation of inmates, while highlighting the distinct characteristics and methodology of the Risale-I Nur in the process of inmate reform, in addition to the enrichment of our understanding of inmates from the perspective of cross-cultural settings.